Program Kota Tanpa Kumuh (Kotaku) Dalam Perspektif Pemberdayaan Masyarakat (studi kasus Program Kota Tanpa Kumuh di Kelurahan Karangwaru) - KHOLQI, AHSANUL; Alfirdaus, Laila Kholid (Journal of Politic and Government Studies, 2020)
The Urban slams appeared because of inability or failure of the public to compete aachieve and have all the needs to support life's necessities. The existence of slums could becaused by the development of the city. Because of that, community development can bealternative solution to complete the problem of slums in Indonesia. Empowerment is a conceptfor giving people's big responsbility about how to work.